Micro Hydropower Potential Assessment for Sustainable Tourism Electrification: A Case Study of Taeno Waterfall, Ambon - Eka Rahmat Mahayani Anthonio Putera Lilipaly; Sefnath J Wattimena; Sefnath J Etwan Sarwuna; Cendy S E Tupamahu; Obednego Dominggus Nara; Hendrik Simon Latumaerissa; Aprilyanto Khouw; Gilbert A Rumalatu; Azmain N Hatuwe (Asosiasi Dosen Muda Indonesia, 2026)
This study evaluates the technical and economic feasibility of micro hydropower development at Taeno Waterfall, Ambon, Indonesia, to support sustainable tourism electrification. Hydrological assessment was conducted using 10-year rainfall data (2014–2023) combined with the National Rural Electric Cooperative Association (NRECA) method to estimate streamflow in the absence of long-term discharge measurements. The results indicate an average annual rainfall of approximately 3619.92 mm and an estimated average discharge of 0.70 m³/s. Flow duration curve analysis produced dependable flows of Q50 = 0.63 m³/s, Q80 = 0.35 m³/s, and Q90 = 0.28 m³/s, confirming adequate water availability for year-round micro hydropower operation. Hydraulic analysis showed a gross head of 24 m with a net head of 22.44 m after accounting for friction and minor losses. Using a design discharge of 0.35 m³/s and an overall efficiency of 75%, the estimated electrical power output is approximately 58 kW, classified as micro hydropower. A crossflow turbine was identified as the most suitable technology due to its compatibility with medium-head and moderate-flow conditions, operational flexibility, and cost effectiveness. Estimated electricity demand for tourism facilities is approximately 30 kW peak load with annual consumption of 66 MWh, indicating that the proposed system can fully meet demand with surplus energy for future expansion. Economic analysis using the Indonesian electricity tariff of 0.086 USD/kWh yields an annual benefit of approximately 19,278 USD and a payback period of about 12 years. The findings demonstrate that Taeno Waterfall possesses strong potential for sustainable renewable energy implementation to support tourism development and local energy resilience.